Etiologies, Cerebral Vasomotion, and Endothelial Dysfunction in the Pathophysiology of Posterior Reversible Encephalopathy Syndrome in Pediatric Patients - Ghali, Michael G. Z.; Styler, Michael J. (Journal of Pediatric Neurology, 2020)
The posterior reversible encephalopathy syndrome was characterized by Hinchey and colleagues in the 1990s. The condition frequently afflicts patients suffering from hematologic and solid organ malignancy and individuals undergoing transplantation. Cases are more frequently described in the adult population compared with children. In the pediatric population, malignancy, transplantation, renal disease, and hypertension represent the most common etiologies. Theories on pathogenesis have centered upon cerebrovascular dysautoregulation with increases in blood–brain barrier permeability. This generates vasogenic edema of the cerebral parenchyma and consequent neurologic deficits. The parietal and occipital lobes are affected with greatest prevalence, though frontal and temporal lobe involvement is frequent, and that of the contents of the infratentorial posterior cranial fossa are occasionally described. The clinical presentation involves a characteristic constellation of neurologic signs and symptoms, most typically inclusive of headache, visual-field disturbances, abnormalities of visual acuity, and seizures. Supportive care, withdrawal of the offending agent, antihypertensive therapy, and prophylactic anticonvulsants affect convalescence in majority of cases. The principal challenge lies in identifying the responsible agent precipitating the condition in patients with malignancy and those having undergone transplantation and thus deciding which medication among a multidrug treatment regimen to withhold, the duration of drug cessation required to effect clinical resolution, and the safety of resuming treatment with the compound. We accordingly reviewed and evaluated the literature discussing the posterior reversible encephalopathy syndrome in children.
Keywords: posterior reversible encephalopathy syndrome; malignancy; chemotherapy; leukemia; mechanisms